Incidence and time trends of childhood hematological neoplasms: a 36-year population-based study in the southern European context, 1983–2018 - Trallero, Jan; Sanvisens, Arantza; Almela Vich, Fernando; Jeghalef El Karoni, Noura; Saez Lloret, Isabel; Díaz-del-Campo, Cristina; Marcos-Navarro, Ana Isabel; Aizpurua Atxega, Amaia; Sancho Uriarte, Patricia; De-la-Cruz Ortega, Marta; Sánchez, María José; Perucha, Josefina; et al. (Frontiers in Oncology, 2023)
Background: Haematological neoplasms (HN) are the first most common childhood cancers worldwide. Currently, there is a lack of updated population-based data on the incidence of these cancers in the Spanish paediatric population. The aim of this study was to describe the incidence and incidence trends of HN in children (0-14 years) in Spain using data from the Spanish Network of Cancer Registries and to compare the results with other southern European countries. Methods: Data were extracted from 15 Spanish population-based cancer registries between 1983 and 2018. Cases were coded according to the International Classification of Diseases for Oncology, 3rd edition, 1st revision, and grouped according to the International Classification of Childhood Cancer, third edition. Crude rates (CR), age-specific rates and age-standardised incidence rates using the 2013 European population (ASRE), were calculated and expressed as cases per 1,000,000 child-years. Incidence trends and annual percentage changes (APC) were estimated. Results: 4,747 HNs were recorded (59.5% boys). Age distribution [n (%)] was: <1 year 266 (5.6%), 1-4 years 1,726 (36.4%), 5-9 years 1,442 (30.4%), and 10-14 years 1,313 (27.6%). Leukaemias were the most common group, with a CR and an ASRE of 44.0 (95%CI: 42.5;45.5) and 44.1 (95%CI: 42.6;45.7), respectively. The CR and ASRE of lymphomas were 20.1 (95%CI: 19.1;21.1) and 20.0 (95%CI: 19.0;21.1), respectively. The comparable incidence rates between our results and those of other southern European countries were similar for lymphomas, while some differences were observed for leukaemias. From 1988 to 2016, the trend in leukaemia incidence was stable for both sexes, with an APC of 0.0 (95%CI: -0.5;0.7), whereas a constant overall increase was observed for lymphoma in both sexes, with an APC of 1.0 (95%CI: 0.4;1.6). Conclusions: Leukaemias are the most common HN in children and their incidence has remained stable since 1988, whereas the incidence of lymphomas has increased every year. Lymphoma incidence is like those of other southern European countries, while leukaemia incidence is similar only to those of south-western European countries. Collaborative cancer registry projects allow assessing epidemiological indicators for cancers such as HN, which help health authorities and clinicians providing more knowledge about these malignancies.